Impact of Macroeconomic Factors on the Market Performance of Indonesia Sharia Stocks - Deden Rizal Riadi; Erna Garnia; T Tahmat (Research Synergy Foundation, 2021)
This paper presents a study on the impact of macroeconomic factors on the market performance of Indonesia sharia stocks that is shown by the JII. The studied macroeconomic factors are the regional and global market indexes, oil price, the FED rate, and the US exchange rate. Regional markets considered in this paper are Singapore and Malaysia. On the other hand, the global markets considered in this paper are Hong Kong, Japan, and the United States of America. For this purpose, we have used global data from the period of 2009-2019. This paper's main contribution is the use of principal component analysis (PCA) to reduce the independent variables. Based on the PCA, it is found that the macroeconomic factors can be simplified into two factors, namely regional and global factors. Moreover, it is found that the oil price, the FED rate, and the US exchange rate have no effect on the sharia stock performance. Based on the regression analysis, it is found that these two factors have a positive impact with a significant level of 24.2%. It is also found that the global factor has a greater effect than the regional factor.